THE DEVELOPMENT OF COMMUNICATION BETWEEN TEACHER AND STUDENT IN TEACHING AND LEARNING PROCESS (Lembaga Penerbitan Universitas Esa Unggul, 2013)
AbstractThe teaching and learning process are the process of communication because there is a process to convey message through transmitter or medium to receiver. The message, information source, transmitter or medium, and receiver are the component of communication. The teaching sources who be explained by teacher is message of communication. The curriculum is one of important as source of message. Information source is usually a teacher. Receiver, book writer, medium procedure, education transmitter medium, messages receiver are student or one to the other. This research answer about the teaching and learning process between student and teacher. The research uses the qualitative method through descriptive method, observation, deep interview, and library study. The outcome of research showed the process of communication in School of Natural Bandung is having good collaboration between theory of education with adventure, and exploration in the nature. School of Natural Bandung has been lying at north of Bandung city. Having beautiful view, rice cultivation, and range of hills. It is also near Curug Dago forest and Cikapundung River.Keywords: Process of communication, teacher and student, learning process